2021
DOI: 10.21203/rs.3.rs-144684/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coronavirus (COVID-19): A Systematic Review and Meta-analysis to Evaluate the Significance of Demographics and Comorbidities

Abstract: Background The unprecedented outbreak of a contagious respiratory disease caused by a novel coronavirus has led to a pandemic since December 2019, claiming millions of lives. The study systematically reviews and summarizes COVID-19’s impact based on symptoms, demographics, comorbidities, and demonstrates the association of demographics in cases and mortality in the United States.Methods PubMed and Google Scholar were searched from December 2019- August 2020, and articles restricted to the English language were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 86 publications
2
9
0
1
Order By: Relevance
“…Similar findings were observed in other studies, including meta-analyses for coronary heart disease and COVID-19 [26,27]. A systematic review and meta-analysis carried out to evaluate the significance of demographics and comorbidities in COVID-19 demonstrated that metabolic diseases, comprising CVD, diabetes, hypertension and respiratory diseases (COPD and others), were the most common comorbidities associated with a severely poor prognosis and severe outcomes [28]. Between March and September 2020, a cross-sectional study carried out in 25 hospitals in the South and Southeast regions of Brazil concluded that the high risk of hospital mortality was associated with having hypertension, being male, ages over 69 years, having kidney disease and for patients who were admitted in the ICU, mortality was 47.6% [29].…”
Section: Plos Onesupporting
confidence: 81%
“…Similar findings were observed in other studies, including meta-analyses for coronary heart disease and COVID-19 [26,27]. A systematic review and meta-analysis carried out to evaluate the significance of demographics and comorbidities in COVID-19 demonstrated that metabolic diseases, comprising CVD, diabetes, hypertension and respiratory diseases (COPD and others), were the most common comorbidities associated with a severely poor prognosis and severe outcomes [28]. Between March and September 2020, a cross-sectional study carried out in 25 hospitals in the South and Southeast regions of Brazil concluded that the high risk of hospital mortality was associated with having hypertension, being male, ages over 69 years, having kidney disease and for patients who were admitted in the ICU, mortality was 47.6% [29].…”
Section: Plos Onesupporting
confidence: 81%
“…Regarding population characteristics, it is unsurprising that age, male sex, active cancer, and current smoking habit were associated with poorer survival, as this has been demonstrated by numerous other studies [9,3035]. The observation that survival was increased in those undergoing surgery during admission or in the 12 weeks prior to presentation is of note, but is potentially due to a better baseline of health.…”
Section: Discussionmentioning
confidence: 80%
“…[ 31 ] Reasons for excluding nine studies are as shown in Table 1 . [ 37 38 39 40 41 42 43 44 45 ] Twenty ( n = 20) reviews[ 14 15 16 17 18 19 20 22 23 24 26 28 29 30 31 32 33 34 36 46 ] reported the association between Obesity and disease severity of covid-19. Out of these, five[ 14 16 23 26 30 ] reported severe disease with poor composite outcomes (including mortality).…”
Section: Resultsmentioning
confidence: 99%